Effect of Basella rubra L. leaf extract on haematological parameters and amylase activity - Shikha Sonkar, Deep; Gupta, Rajiv; Saraf, Shubhini A. (Pharmacognosy Communications)
Introduction: Basella rubra is a plant species commonly known as Poi (family Basellacea) found in almost every part of India, except hills. Poi possesses several folkloric uses, having beneficial effects in haemorrhagic diseases and as a tonic. In the present study, the effects of ethanolic and aqueous extract of Basella rubra (Poi) leaves were investigated for haematological parameters on normal Swiss mice and amylase activity on Wistar rats. Methods: Ethanolic and aqueous extracts of the plant (dosed at 100 and 200 mg/kg body weight) were administered to mice in different test groups for a period of 14 days for determination of haematological parameters. Aqueous, ethanolic and hexane extracts were given (200 mg/kg body weight) to the test group animals (Wistar rats) for the determination of amylase activity. The control group received distilled water for a period of 7 days. Result: There was an increase in the haematological parameters (RBC, WBC, Hb and PCV. The plant extracts caused a significant increase in the total bilirubin content. The aqueous and ethanolic extracts of 200 mg/kg showed significant increase (P < 0.05) in total bilirubin content but no significant increase was observed in aqueous and ethanolic extract (100 mg/kg) treated mice. There was also an increase in the amylase content in the hexane and ethanolic group animals and a decrease of amylase content in aqueous extract containing animals as compared to control group. Conclusion: It can be concluded that the commom plant B. rubra leaf has beneficial haematological properties in Swiss mice. In addition, the extract can prevent various complications of diabetes.
Keywords: Basella rubra; Poi; haematological parameters; amylase activity